Effect of heat-treatment on microstructure of hydroxyapatite porous microspheres for enhanced biocompatibility - Wei-li Xu; Xue-hui Sun; Dong Xue; Ji-zhao Guo; Xin-ke Yan; Pei-jian Sun; Yi Cao; Mei-li Qi; Cong Nie (Journal of Saudi Chemical Society)
Abstract An in-depth exploration into the impact of heat-treatment on the microstructure of HA microspheres is imperative to enhance their biocompatibility, a prerequisite for the development of high-performance HA biomaterials. In this study, the impact of heat-treatment at 600–1000 °C on the microstructure and biocompatibility of HA porous microspheres prepared by the hydrothermal method was investigated. The results showed that the microsheet-assembled HA porous microspheres with diameters of approximately 40–120 μm were obtained. The crystallinity of HA porous microspheres increased with the rise of heat-treatment temperature while the specific surface area and particle size decreased. SEM and TEM observations indicated that the pore size and through porosity of HA microspheres increased under high temperature conditions based on the mechanism of fusion growth of grains. The CCK-8 assay and Live/Dead staining evaluations revealed that heat-treatment promoted the biocompatibility and bioactivity of HA porous microspheres. This study provides new concepts for the controllable optimization of the microstructure and biological properties of HA materials to broaden their clinical applications.